Third head of biceps femoris muscle-a case report - Ghatak, Surajit; Adole, Sonali; Deka, Debajani; Faizal, Muhamed (International Surgery Journal, 2021)
Sometimes variations in biceps femoris may be noticed like an accessory head of biceps femoris. Here during routine cadaveric dissection in the department of anatomy. All India institute of medical sciences, Jodhpur we found a case with an accessory head of biceps femoris in both the lower limbs. The muscle belly is originating from the fibers of long head of biceps femoris and going downward medially to get inserted to the medial condyle of tibia on its medial superior aspect. On the right-side insertion site is like a sheath and on half a way it is merging with medial intermuscular septum of thigh. On the left side insertion is first like a thin sheath and then a thin muscle belly. The muscle belly is thin as compared to the long and short head of the main muscle bellies. On the left side thickness is around 3.7 mm in the upper end and thinner in the lower end while on right side also it is around 3.75 mm. On right side length of muscle belly is around 5 cm and on left side it is around 5.5 cm muscle belly, then becomes a sheath with length around 0.5 mm and then again becomes a muscle belly of around 3.5 cm length. Short head is arising high up on the left side while on right side it is as normal.